2017
DOI: 10.1159/000458522
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Isolated First-Trimester Fetal Megacystis with Spontaneous Resolution

Abstract: Objective: Fetal megacystis has a poor prognosis. During the first trimester, it is frequently associated with chromosomal abnormalities or multiple malformations, but can also be isolated and resolve spontaneously. In this study, our main objective was to determine the fetal and pediatric prognosis in this particular situation. Methods: This was a retrospective multicenter study. We describe the cases referred to our fetal medicine centers and also cases previously reported in the international literature. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Fontanella et al reported in 2017 [ 19 ] that diameter bladder is a predictor of spontaneous resolution if the diagnosis is made before 18 weeks (80% sensitivity and 79% specificity). They specified that spontaneous regression before 23 weeks is a marker of favorable neonatal outcome, without urological surgical intervention, which is consistent with the 2017 study by Girard et al [ 29 ].…”
Section: Discussionsupporting
confidence: 78%
“…Fontanella et al reported in 2017 [ 19 ] that diameter bladder is a predictor of spontaneous resolution if the diagnosis is made before 18 weeks (80% sensitivity and 79% specificity). They specified that spontaneous regression before 23 weeks is a marker of favorable neonatal outcome, without urological surgical intervention, which is consistent with the 2017 study by Girard et al [ 29 ].…”
Section: Discussionsupporting
confidence: 78%
“…In a study of 16 first trimester megacystis cases only two were associated with oligohydramnios, all had a bladder size greater than 9 mm, 10 were associated with additional findings, and four had abnormal karyotype (2 cases of trisomy 13, one case of trisomy 18 and one case of trisomy 21) 3 . Spontaneous resolution of first trimester megacystis has been described in the literature, with a 2.4% risk of chromosomal abnormalities in such cases and normal pediatric follow‐up in 96.4% of cases 4 …”
Section: Fetal Megacystis and Lower Urinary Tract Obstruction (Luto)mentioning
confidence: 94%
“…3 Spontaneous resolution of first trimester megacystis has been described in the literature, with a 2.4% risk of chromosomal abnormalities in such cases and normal pediatric follow-up in 96.4% of cases. 4 Fetal lower urinary tract obstruction (LUTO) occurs in 2.2-3.4 of 10,000 live births, but the incidence is higher owing to fetal loss. 5,6 The clinical course of LUTO is variable and dependent on etiology, duration, and age at onset of the obstruction.…”
Section: Fetal Megacystis and Lower Urinary Tract Obstruction (Luto)mentioning
confidence: 99%
“…113 An enlarged bladder (length in the sagittal plane of ≥7 mm) has been associated with aneuploidy and lower urinary tract obstruction; however, in the euploid fetus, it may be a transient finding with a good outcome. 26,113,114 Fetal Spine and Extremities The fetal extremities are easily visible between 12 weeks 0 days and 13 weeks 6 days. 115 Major limb reduction anomalies can be detected at this gestational age.…”
Section: Fetal Neckmentioning
confidence: 99%
“…In some euploid fetuses, there is delayed return of the bowel into the abdominal cavity without other complications 113 . An enlarged bladder (length in the sagittal plane of ≥7 mm) has been associated with aneuploidy and lower urinary tract obstruction; however, in the euploid fetus, it may be a transient finding with a good outcome 26,113,114 …”
Section: Specifications Of the Examinationmentioning
confidence: 99%